Exploring the Pathways and Practical Analysis of Digital-Intelligent Transformation in Application-Oriented Higher Education: A Case Study of the "Technology-Discipline-Application" Integration Model at Qingdao Hengxing University of Science and Technolog - Tiantian, Tang (International Conference on Fundamental and Applied Research (I-CFAR), 2026)
Faced with the wave of digital-intelligent transformation in education, how application-oriented universities can break through the disconnection between “technological instrumentalization” and “traditional teaching” has become a key issue in educational reform. This study takes Qingdao Hengxing University of Science and Technology as a typical case, proposing and validating a “Technology–Discipline–Application” three-dimensional integration model driven by “authentic application.” This model establishes a digital foundation through building the “Hengxing Capacity Platform + high-end experimental centers” (Technology), restructures the curriculum system around “project-based and studio-based approaches” (Discipline), and embeds real-world commercial projects such as “brand operations, film and television production, and live-streaming e-commerce” (Application), thereby achieving deep integration of industry and education. The study finds that using “authentic application” as a value anchor can reversely reconstruct the teaching system and organizational model; the dual-base architecture of “platform + scenarios” effectively promotes the synergistic empowerment of technology, knowledge, and ability; and the educational ecology of “teachers as mentors, students as creators, and works as products” significantly enhances the quality and adaptability of talent cultivation. This research provides replicable practical pathways and theoretical insights for resolving the structural contradictions in the digital-intelligent transformation of application-oriented universities.